Respostas

2013-11-10T11:36:47-02:00
A)4^{x}-2^{(x+2)}+3=0
(2^{2})^{x}-2^{x}*2^{2}+3=0
(2^{x})^{2} - 2^{x}*4+3=0
2^{x}=a
a^{2} -4*a+3 =0

raízes de a são os valores de 3 e 1

2^{x} = 3

\log_2 2^x = \log_2 3

como \log_2 3 = 0,6 e \log_2 2 = 1

x
\log_2 2 = \log_2 3
x = 0,6 

2^x = 1

2 ^x = 2^0
x= 0


b) (\log_2 x)^{2} - (\log_2 x)^{3} + 2 = 0
2 (\log_2 x) - 3 (\log_2 x) + 2 =0
\log_2 x = a
2 a - 3 a +2 =0
-a = -2
a = 2

Voltando a substituição feita anteriormente ...

\log_2 x = 2
2 ^{2} = x
4 = x